Defects in CsPbX3 Perovskite: From Understanding to Effective Manipulation for High‐Performance Solar Cells. Issue 11 (19th September 2021) - Zhang, Jingru; Zhao, Wangen; Olthof, Selina; Liu, Shengzhong (Frank)
Abstract: The rapid development of all inorganic metal perovskite (CsPbX3, X represents halogen) materials holds great promise for top‐cells in tandem junctions due to their glorious thermal stability and continuous adjustable band gap in a wide range. Due to the presence of defects, the power conversion efficiency (PCE) of CsPbX3 perovskite solar cells (PSCs) is still substantially below the Shockley‐Queisser (SQ) limit. Therefore, it is imperative to have an in‐depth understanding of the defects in PSCs, thus to evaluate their impact on device performances and to develop corresponding strategies to manipulate defects in PSCs for further promoting their photoelectric properties. In this review, the latest progress in defect passivation in the CsPbX3 PSCs field is summarized. Starting from the effect of non‐radiative recombination on open circuit voltage ( V oc ) losses, the defect physics, tolerance, self‐healing, and the effect of defects on the photovoltaic properties are discussed. Some techniques to identify defects are compared based on quantitative and qualitative analysis. Then, passivation manipulation is discussed in detail, the defect passivation mechanisms are proposed, and the passivation agents in CsPbX3 thin films are classified. Finally, directions for future research about defect manipulation that will push the field to progress forward are outlined. Abstract : This review summarizes the latest progress in defect passivation in the CsPbX3 (X represents halogen) perovskite solar cells field. Starting from the effect of non‐radiative recombination on open circuit voltage losses, the defect fundamentals, techniques to identify defects, passivation mechanisms, and strategies are discussed. Finally, directions for future research about defect manipulation that will push the field to progress forward are outlined.